A comparison of the Antileukaemic Effects of Recombinant Human Tumour Necrosis Factor-α and its Muteins on Leukaemia L1210 and Leukaemia P388 in Mice. Issue 6 (1994) - Warzocha Warzocha, K. K.; Góra-Tybor Góra-Tybor, J. J.; Kwinkowski Kwinkowski, M. M.; Szymańska Szymańska, B. B.; Robak Robak, T. T.
Abstract : We investigated the influence of recombinant human tumour necrosis factor alpha (TNF-α) and its derivatives termed muteins III, V, VI—in which the first 3 to 7 amino acids of native TNF-α have been replaced—on the survival time of mice inoculated with leukaemia L1210 or leukaemia P338. TNF-α prolonged the survival of mice with leukaemia L1210 but did not have any therapeutic activity in leukaemia P388-bearing mice. Muteins-treated mice with leukaemia P388 lived longer than animals receiving TNF-α, while those inoculated with leukaemia L1210 did not show any significant prolongation of life compared with the TNF-α treated group. The results presented in this report indicate that the antileukaemic activity of TNF-α is governed at least in part by the nature of the N-terminal amino acids.